1965
DOI: 10.1071/ph650023
|View full text |Cite
|
Sign up to set email alerts
|

A Spectroscopic Study of a Decaying Hydrogen Plasma

Abstract: SummaryA study has been made of the decay of a hydrogen plasma of ion density .--3 X 1015 cm-3 and temperature .--10' oK. Details are presented of the experimental methods used to determine density and temperature distributions in the decaying plasma. The plasma decays by three-body recombination mainly and the experimental values of the recombination coefficient agree with those expected for a plasma opaque to Lyman radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

1965
1965
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 7 publications
3
3
0
Order By: Relevance
“…This result has also been observed by Cooper and Kunkel [22], Irons and Millar [19] and Forman [23] who find that in a rotating plasma, approximately one-third of the total number of protons in the original hydrogen molecules are lost from the main body as neutrals. In his elegant measurements of atomic hydrogen densities, Forman [23] shows that this atomic hydrogen is lost during the ionization process and returns to the centre of the plasma well after the transit time of the shock wave.…”
Section: Loss Of Particles During Ionization Processsupporting
confidence: 79%
See 1 more Smart Citation
“…This result has also been observed by Cooper and Kunkel [22], Irons and Millar [19] and Forman [23] who find that in a rotating plasma, approximately one-third of the total number of protons in the original hydrogen molecules are lost from the main body as neutrals. In his elegant measurements of atomic hydrogen densities, Forman [23] shows that this atomic hydrogen is lost during the ionization process and returns to the centre of the plasma well after the transit time of the shock wave.…”
Section: Loss Of Particles During Ionization Processsupporting
confidence: 79%
“…Spectroscopic temperature measurements were attempted by using the technique employed by Irons and Millar [19] to compare the H y line intensity with bands of continuum radiation free from impurity lines centred at wavelengths of 5094 A and 3440 A. The intensities of the two continuum radiation bands were also compared with each other.…”
Section: Electron Temperaturementioning
confidence: 99%
“…A value of about 1· 6 X 10 15 cm-3 is obtained. This is in reasonable agreement with that expected from the results of Irons and Millar (1965), who have made a detailed investigation of the density and temperature distributions in a similar but smaller machine (Supper I). Their results also enable an estimate to be made of the temperature in Supper II, which has not been measured spectroscopically.…”
Section: (D) Plasma Propertiessupporting
confidence: 81%
“…Also shown are the finally selected theoretical curves; these have the following parameters: total particle density 2·1 X 1015 cm-3, fractional ionization 0·5, temperature 1·2 X 104°K, cross sections A 5'0, B 10·0 X 10-15 cm2 • It is at first surprising that the percentage ionization is about the same for all three wave times; one may have expected this to fall off with time. Irons and Millar (1965) have shown that the plasma decay process occurs much faster in the outer, cooler layers of the plasma, and this leads to a shrinkage in diameter of the central plasma column, within which the density and temperature fall off very slightly during the times of interest. Framing camera photographs show no apparent change in the diameter of the central core.…”
Section: S 50mentioning
confidence: 99%
“…The radially averaged be4 at the firing electrode is thus given by 3.4. ELECTRON TEMPERATURE Spectroscopic temperature measurements were attempted by using the technique employed by Irons and Millar [19] to compare the H y line intensity with bands of continuum radiation free from impurity lines centred at wavelengths of 5094 A and 3440 A. The intensities of the two continuum radiation bands were also compared with each other.…”
Section: Shock Velocitymentioning
confidence: 99%